Performance of a Noninvasive Time-Harmonic Elastography Technique for Liver Fibrosis Evaluation Using Vibration Controlled Transient Elastography as Reference Method - Moga, Tudor Voicu (Diagnostics (Basel), 2020)
Aim: This study aimed to evaluate the diagnosis performance of time-harmonic elastography (THE) technique in real life in assessing liver fibrosis, considering vibration-controlled transient elastography (VCTE) as a reference method. Material and Method: We prospectively evaluated outpatients from the gastroenterology department. Liver stiffness (LS) was measured by the THE system by dedicated operators, and by VCTE by experienced operators. The diagnostic accuracy of THE in staging liver fibrosis was assessed. We also performed an intra- and interobserver reproducibility sub-analysis on a sub-group of 27 subjects, where liver stiffness measurements (LSM) were performed by a novice, an elastography expert, and an ultrasound expert. Results: Of the 165 patients, using VCTE cut-off values, 49.6% were F0-F1, 15.7% were F2, 6.6% were F3, and 28.1% were F4. A direct, significant and strong correlation (r = 0.82) was observed between LSM assessed by VCTE and THE, p < 0.0001. The cut-off for ruling out liver cirrhosis (LC) by THE on our study group was <1.61 m/s (7.77 kPa)–AUROC = 0.90 [95% CI (0.82–0.93)], Se = 90.7%, Sp = 66.6%, PPV = 55.7%, NPV = 93.9%. The cut-off for ruling in LC by THE was >1.83 m/s (10 kPa)-AUROC = 0.90 [95% CI (0.82–0.93)], p < 0.0001, Se = 65.1%, Sp = 96.7%, PPV = 90.3%, NPV = 85.7%. The overall agreement between examiners was excellent: 0.94 (95% CI: 0.89–0.97); still, the ICCs were higher for the more experienced elastography examiner: 0.92 (95% CI: 0.82–0.96) vs. 0.94 (95% CI: 0.87–0.97) vs. 0.97 (95% CI: 0.95–0.99). Conclusions: THE is a feasible and reproducible elastography technique that can accurately rule in and rule out advanced liver disease.